Guillermo Tolentino's Grupo de Filipinos Ilustres and the Making of a National Pantheon - Mojares, Resil B. (2010)
The essay inquires into the contingencies, gaps, and tensions in the process of "pantheonization," or the canonization of national heroes, by taking up the case of Guillermo Tolentino's Grupo de Filipinos Ilustres (1911). From the analysis of a portrait, it widens into a reflection on the formation of civic nationalism in the early twentieth century as Filipino intellectuals and the U.S.-sponsored government sought to create a "nation-space" through projects of defining a "national" history, language, literature, music, theater, dance, art, and others.
Keywords: Printmaking; Photography; Canonization; Heroes